THE CORRELATION BETWEEN VOCABULARY MASTERY AND DESCRIPTIVE PARAGRAPH WRITING ABILITY OF THE EIGHTH GRADE STUDENTS - Ni Kadek Ari Yasmini; Dewa Ayu Ari Wiryadi Joni; Dewa Gede Agung Gana Kumara (Academic Journal on English Studies (AJOES), 2022)
This study dealt with the correlation between students’ vocabulary mastery and descriptive paragraph writing ability. The study carried out in grade 8D and 8F of SMP N 1 Kuta Utara in academic year 2021/2022. The purpose of this research was to find out whether there was significant correlation between students’ vocabulary mastery and descriptive paragraph writing ability. The present study used an ex-post facto research with correlational design. The population of the present study consisted of 404 students and the samples were 68 students. The researcher used two tests to get the data of vocabulary mastery and descriptive writing ability, such as procedure rational deletion cloze task items for vocabulary mastery and picture description test for the descriptive paragraph writing ability. The obtained data were assessed by using Pearson Product Moment Correlation and analyzed by using SPSS 25.0. Based on the data analysis, it showed that there is a very high, positive and significant correlation between vocabulary mastery and descriptive paragraph writing ability of the eighth-grade students of SMP N 1 Kuta Utara in academic year 2021/2022. Therefore, it answered the research question that there is a significant correlation between vocabulary mastery and descriptive paragraph writing ability.